Screening of canola (Brassica napus L.) cultivars for nickel stress tolerance - Hummera Nawaz; Ameer Khan; Aamir Ali; Amna Ameer (International Journal of Applied and Experimental Biology)
The present study was conducted to evaluate variation in nickel stress tolerance in a set of 10 canola cultivars (Leand, AC Excel, Faisal Canola, Shiralee, Oscar, Punjab Canola, CON-II, Rainbow, Dunkeld, and Cyclone) at the early growth stages, i.e., germination and seedling stage. The seeds of all canola cultivar were obtained from the Ayub Agricultural Research Institute, Faisalabad, Pakistan. Ten seeds of each cultivar were sown in each of Petri plates moistened with varying levels (15, 30 and 45 mg/L) of nickel in Hoagland nutrient solution. Data for different growth indices were recorded such as germination stress index (GSI), shoot length stress index (SLSI), root length stress index (RLSI), and seedling fresh (SFWI) and seedling dry weight indices (SDWI). Based on different growth indices, three canola cultivars, i.e., CON-II, Faisal Canola and Leand proved to be potential source of variation for Ni tolerance provided if they maintain their degree of Ni tolerance at the later growth stages. However, Oscar was the most sensitive to Ni stress of all 10 cultivars evaluated in the current study.